(untitled) (El-Wahat Journal for Research and Studies, 2017)
The present research aims at indicating what stages the International Protection of Refugees underwent. Note that both World War I and World War II resulted in the introduction of the term ‘refugee’ for the first time. The two wars, moreover, had left huge destruction and spread of vagrants’ numbers in the word especially in Europe. The present research also praises the efforts made by the international community to contain the situation, starting from the League of Nations to the United Nations, not forgetting to state to what extent every attempt in the course was successful. The research also questions what UN Refugees has done towards refugees, since the United Nations’ major aim is to enforce the law that protect refugees. Take 1951’s Treaty and a sample protocol of 1967 as an example. Key words- International community, United Nations High Commissioner for Refugees